Blood metabolism study on protection of residual renal function of hemodialysis patients by traditional Chinese medicine Kidney Flaccidity Compound - Hu, Qiong-dan; Wu, Wei-hua; Zeng, Yan; Wen, Ji; Li, Xiao-jun; Pan, Wei; Zhang, Mao-ping; Hu, Bo; Lei, Chun-yan; Fan, Junming (Cellular and Molecular Biology, 2018)
In recent years, metabolomics using high-performance liquid chromatography (UPLC) has been used to study the metabolic profiles in plasma, urine, stool and tissue in animal model of chronic kidney disease (CKD). In the previous work, we found that traditional Chinese medicine (TCM) "Kidney Flaccidity Compound” (KFC) based on "kidney flaccidity theory” can improve renal function and quality of life of patients with kidney disease. This study aimed to investigate the metabolic profiles in peripheral blood of hemodialysis patients administrated by KFC for 1.5 and 3 months and explore the potential metabolic mechanism using UPLC. Results showed that 121 metabolites were different between KFC 3-months group and untreated control, of which 75 were significantly upregulated and 46 were significantly downregulated. In the 1.5-months treatment group, there were 365 metabolites, of which 164 were significantly upregulated and 192 downregulated. There were 6 metabolites and 15 metabolites upregulated 3-fold in 3-months and 1.5-months KFC treatment group, respectively. In addition, more than 60 new metabolites were identified in the peripheral blood in KFC treated patients, including two potential diagnostic markers MGDG 30:8 and 2-(hydroxymethyl)-6-[[(1R,4S) -2,2,4-trimethyl-3-oxabicyclo[2.2.2]octan-5-yl]oxy]oxane-3,4,5-triol. The pathway enrichment analysis showed thce differential metabolites mainly enriched in Arginine and proline metabolism, Urea cycle, Tyrosine metabolism, Methionine metabolism, Tricarboxylic acid cycle, and Androgen and estrogen metabolism. The findings are helpful to reveal the mechanism of KFC protects CKD, and to provide a new strategy for recovery renal function in hemodialysis patients.